The Dichotomy of Traditional Cuisine Protection in Indonesia: Geographical Indications vs. Traditional Knowledge - Disemadi, Hari Sutra; Sudirman, Lu; Tan, David; Situmeang, Ampuan (Jurnal Hukum Novelty, 2023)
Introduction to The Problem: Traditional cuisines are an important part of national identity in Indonesia and a significant driver in the tourism industry, which are currently threatened by the constantly accelerating waves of globalization.Purpose/Objective Study: This research aims to analyze the ways to protect traditional cuisines through the intellectual property law, comparing the regime of GI and traditional knowledge, as suitable options of protection.Design/Methodology/Approach: This research utilizes normative legal research method, with statutory approach. To support this method, this research also utilizes literature analysis and comparative analysis technique to analyze the dichotomy between Geographical Indication and Traditional Knowledge.Findings: Analysis finds that the GI regime comes out as the superior regime of protection from the dichotomy, with lesser normative loopholes. Authenticity plays an important role in the comparative analysis between the two regimes, as it’s normatively backed as an important part of the tourism sector. Further analysis also finds that the GI regime can still be improved, particularly regarding substantive examination, which needs more definitive provisions to guarantee authenticity of traditional cuisines in Indonesia.Paper Type: Research Article